Ketahanan Pangan Remaja Putri di Pondok Pesantren As’ad Kota Jambi - Iin Indrawati; Siti Fati Hatussaadah; Maryam Novitasari; Muhammad Hidayat (3031-8572, 2025)
Adolescence is the age of growth, when many body parts and organs develop rapidly and determine their health as adults. Adolescent girls need around 2,200 to 2,500 calories per day, while adolescent boys need around 2,400 to 3,000 calories per day. The purpose of this study was to see the picture of food security of students at the As'ad Islamic Boarding School in Jambi City. This study is a quantitative study with a descriptive analytical design. The population of this study was all students of the As'ad Islamic Boarding School with a level of Madrasah Tsanawiyah Education totaling 375 female students using the proportional Random Sampling technique, the number of samples was 29 students. The results of the study showed data of 13 (44.8%) female adolescents who routinely had breakfast, and those who rarely had breakfast were 14 (48.3) and never had breakfast 1 (3.4%), 28 (96.6%) female adolescents who chose good types of breakfast and 1 less good, 22 (75.9%) female adolescents who ate snacks and 7 (24.1%) did not eat snacks, and all female adolescents consumed main meals according to those provided by the dormitory kitchen manager.